The Stanford Faculty Development Center End-of-Life (ELC) Curriculum - James Hallenbeck (Association of American Medical Colleges, 2006)
Abstract Introduction Until recently, end-of-life care (ELC) has been neglected in physician training. This has resulted in difficult dying experiences for patients, their families, physicians, and other health care workers. The goals of this curriculum are to enhance physician skills in ELC; foster commitment to improving care for the dying; improve the dying experience for patients, families, and health care providers; and improve teaching related to ELC. Methods This resource contains eight 2-hour sessions, designed to be administered over a 30-day period. The module topics address the following areas: death and dying in the US, pain management, communicating with patients and families, making difficult decisions, non-pain symptom management, venues and systems of care, psychiatric issues and spirituality, and instituting change. PowerPoint slides sets and an extensive 155 page teaching guide with in-depth notes on how to teach the curriculum and a discussion of particular challenges that arise in teaching specific content areas are provided to facilitate instruction. The teaching guide also includes supporting material such as bibliographies. Results Between 1999 and 2002, 16 faculty members were formally taught this course over a 1-month intensive training period. To date they have in turn taught over 3,400 trainees. We have collected pre-/postdata from faculty and some trainees, which demonstrate significant increases in self-assessed knowledge, skill, and confidence in this area. Since posting of the curriculum on the web, thousands of downloads of the curriculum and handbook have occurred. In January 2004, 1,611 copies of the modules and 1,139 copies of the handbook were downloaded. Discussion While a host of ELC curricula have been developed in recent years, ours is unusual in its attention to certain content areas (e.g., spirituality) and the attention paid to pedagogy. The publication of the curriculum with the detailed teaching guide can be seen as an attempt to provide broader exposure to the curriculum. The process and approach used in this faculty development project built upon tested methods used for prior projects by the Stanford Faculty Development Program. Learning how to adapt general principles of adult learning theory to specific educational challenges in teaching ELC was a particularly interesting part of curriculum development. Many development and implementation challenges are discussed in the teaching guide.